Synthesis of enantiomerically pure (R)-and (S)-1-benzoyloxypropane-2,3-diol and revision of the stereochemical outcome of the Candida antarctica lipase-catalyzed benzoylation of glycerol - CASATI, SILVANA; P. Ciuffreda; E. Santaniello (Tetrahedron: Asymmetry, 2011)
Enantiomerically pure (R)- and (S)-1-benzoyloxypropane-2,3-diol have been prepared from (S)-(+)-2,2-dimethyl-1,3-dioxolane-4-methanol and used as reference compounds to correct the reported stereochemical outcome of the Candida antarctica lipase (CAL)-catalyzed benzoylation of glycerol.